Relationship Relationship Of Physical Activity With Sleep Quality Of Chronic Renal Failure Patients That Are Taking Hemodialysis - Achwan Achwan; Muhammad Daffa Noverio; Dwi Agustina (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
ABSTRACT Background: CKD patients have nervous and muscular system disorders that affect sleep quality. The quality of sleep is influenced by many factors, one of which is physical activity. Active physical activity is known to improve sleep quality. Purpose: to determine the relationship between physical activity and the sleep quality of CKD patients undergoing hemodialysis at Haji Hospital Jakarta in 2022. Method: The research design used was cross-sectional with a total of 96 respondents selected by purposive sampling. The independent variable of physical activity was measured with the GPAQ while the sleep quality as dependent variable with the PSQI. Results: Respondents with active physical activity at 47.9% and respondents with good sleep quality at 33.3%. The distribution of respondents who had active physical activity with good sleep quality was 43.5% while those who were inactive had good sleep quality at 24.0%. The statistical test yielded a p-value (α=95%) of 0.043 and an Odd Rasio value of 2.4. Conclusion: Physical activity has a significant relationship with the sleep quality of CKD patients undergoing hemodialysis. CKD patients whose physical activity is active are 2.4 times more likely to have better sleep quality than inactivity. Keywords: Physical Activity; Sleep Quality; CKD; Hemodialysis.